Identification and Characterization of the dps Promoter of Mycobacterium smegmatis: Promoter Recognition by Stress-Specific Extracytoplasmic Function Sigma Factors σ(H) and σ(F) - Chowdhury, Rakhi Pait (American Society for Microbiology (ASM), 2007)
The survival of a bacterium with a depleted oxygen or nutrient supply is important for its long-term persistence inside the host under stressful conditions. We studied a gene, dps, from Mycobacterium smegmatis, encoding a protein, Dps (for DNA binding protein from starved cells), which is overexpressed under oxidative and nutritional stresses and provides bimodal protection to the bacterial DNA. Characterization of the dps promoter in vivo is therefore important. We cloned a 1-kb putative promoter region of the dps gene of M. smegmatis in an Escherichia coli-Mycobacterium shuttle vector, pSD5B, immediately upstream of the lacZ gene. Promoter activities were assayed in vivo both in solid medium and in liquid cultures by quantitative β-galactosidase activity measurements. To characterize the minimal promoter region, a 200-bp fragment from the whole 1-kb sequence was further cloned in the same vector, and in a similar way, β-galactosidase activity was quantitated. Primer extension analysis was performed to determine the +1 transcription start site of the gene. Point mutations were inserted in the putative promoter sequences in the −10 and −20 regions, and the promoter sequence was confirmed. The promoter was not recognized by purified M. smegmatis core RNA polymerase reconstituted with purified Mycobacterium tuberculosis σ(A) or σ(B) during multiple- and single-round in vitro transcription assays. Promoter-specific in vivo pull-down assays with an immobilized 1-kb DNA fragment containing the dps promoter established that extracellular function sigma factors were associated with this starvation-inducible promoter. Single-round transcription at the dps promoter further supported the idea that only core RNA polymerase reconstituted with σ(F) or σ(H) can generate proper transcripts.